A study on the syntactic and semantic features of the English verbs “look”, “see”, “watch” with reference to their Vietnamese equivalents / Đỗ Thị Toan; NHDKH Dang Ngoc Huong, Ph.D - Đỗ, Thị Toan
This research is conducted to achieve the targets of finding out syntactic and semantic features of English verbs: look, see, watch with reference to the Vietnamese equivalents as well as suggesting some possible implications for learning and teaching these English verbs. To carry the study, the author uses both qualitative and quantitative approaches . Numerous examples have been analyzed cautiously by applying qualitative approach and some other ones so as to achieve the set objectives. Through a small test made in Nguyen Du secondary school, It is found that high percentage of errors was made by misunderstanding the syntactic and semantic features of the English verbs look, see, watch. Most of them don’t understand clearly about the sentence pattern of these verbs. These findings can lead to the conclusion that different meanings created by one lexeme are caused by different contexts in which senses of the exist. This proves the fact that providing students with meanings of each verb must be clearly given in concrete contexts with proper Vietnamese references.